Estudio de factibilidad para la creación de un restaurante online de comida saludable, con elaboración donde los clientes lo determinen, en la ciudad de Bogotá, D.C (2020)
In the present feasibility study, for the creation of an online restaurant for healthy food, with elaboration where customers determine it, in the city of Bogotá, DC, the respective analysis of opportunities offered by the service sector and the subsector was carried out. of restaurants, this through a PESTAL analysis in Colombia and in the city of Bogotá, to later establish the competitive advantages of the mentioned sector and subsector, in order to start a market study that would allow the respective product description to be made for this case is a service and food preparations proposed on the menu available to customers, this in order to identify the scope of Porter's forces; Carrying out the correct market segmentation, where the target population was determined under a series of selected characteristics, in order to carry out market research, where data were obtained for the analysis of demand, supply and competition so that the business idea was made known through the respective strategies determined through the marketing mix and the scope of digital marketing.